2022
DOI: 10.1128/spectrum.01468-22
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Colistin Combined with Amikacin or Levofloxacin against Pseudomonas aeruginosa Biofilm Infection

Abstract: Infections associated with PA biofilm formation are extremely challenging. When monotherapy fails to achieve optimal efficacy, combination therapy becomes the last option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Thus, Gómez-Juyent, J et al reported that these combinations were the most appropriate treatments for biofilm-related infections [ 54 ] and Armengol, E et al showed how COL enhances rifampicin’s antimicrobial activity in COL-resistant biofilms [ 55 ]. Wang Y et al validated the effectiveness of the AMK–COL combination not only in vitro but also in an animal biofilm infection model [ 56 ]. Other antibiotic combinations have also been reported to be more effective than monotherapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Gómez-Juyent, J et al reported that these combinations were the most appropriate treatments for biofilm-related infections [ 54 ] and Armengol, E et al showed how COL enhances rifampicin’s antimicrobial activity in COL-resistant biofilms [ 55 ]. Wang Y et al validated the effectiveness of the AMK–COL combination not only in vitro but also in an animal biofilm infection model [ 56 ]. Other antibiotic combinations have also been reported to be more effective than monotherapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The carbapenem-resistant and bioluminescent strain PAO1 (CRPAO1) was cultured as previously described. 14 PA ATCC 27853 was used as a quality control strain.…”
Section: Methodsmentioning
confidence: 99%